Youth academic achievement, social context, and body mass index - Lauren Gaydosh; Sara McLanahan (Elsevier, 2021)
This study assesses the relationship between academic achievement and body mass index for age (BMI) trajectories across childhood and adolescence, and investigates how this relationship is moderated by social context. Specifically, we test the hypothesis that academic achievement is not associated with improved BMI among youth from disadvantaged social contexts. We test for differences by race/ethnicity, and examine the role of county-level economic mobility in shaping these patterns. We use data from the longitudinal Fragile Families and Child Wellbeing Study (FFCWS), an ongoing birth cohort study representative of children born in large US cities in 2000, and measure BMI, academic achievement, and social context at Years 5, 9, and 15. Estimating multilevel random effects linear regression models of BMI from childhood to adolescence, we find that youth who were exposed to social advantage displayed a negative association between academic achievement and BMI. In contrast, youth exposed to social disadvantage displayed no association between academic achievement and BMI. This difference was observed regardless of race/ethnicity. County-level economic mobility modified the observed relationship, such that youth living in places with low levels of mobility displayed higher BMI associated with high academic performance. The results suggest that the health costs of academic achievement among disadvantaged youth are concentrated in areas with low institutional support for upward mobility. The findings demonstrate that the unequal benefits of educational attainment begin early in life, while living in places that promote upward mobility can help individuals realize the health benefits of their own educational attainment.